The productivity of various pure breed and cross breed of imported pigs during lactation period - Aritonang, Djamuara; Silalahi, Marsudin (Indonesian Animal Sciences Society, 2001)
A study has been conducted to evaluate the productivity of pure breeds and cross breeds of imported pigs. Sixteen strains of pigs with five best sows were selected based on litter size and birth weight on the second parity. The results of the study showed that the pure breed performance was better than the cross breeds, as shown by the litter size, birth and weaned weight, less mortality, better mothering ability and better feed efficiency. Between pure breed, the Landrace and Yorkshire were better than other sows and between the cross breed, the LH and YL performed better than other crossbreeds. It is recommended that the pure breed especially Landrace and Yorkshire and LH and YL of cross breed are better than others Â Key words: Productivity, imported pigs, lactation